A new fluorescent probe for ultrasensitive detection of phosgene in solution and the gas phase. (12th March 2021) - Zeng, Fenfen; Bao, Guangbo; Zhou, Baocheng; Han, Yifeng
Abstract : A new fluorescent probe has been developed for sensitive and selective detection of phosgene in solution and vapor. Abstract : Due to the high toxicity and commercial availability of phosgene, it is urgent to detect phosgene quickly and reliably to deal with its potential serious threat to public safety. A new 2-(2-aminophenyl)quinazolin-4(3 H )-one (APQ ) based fluorescent probe APQ has been developed as a rapid, highly sensitive, and selective sensor for phosgene in this work. APQ displays very weak fluorescence in acetonitrile due to the free rotation of the 2-aminophenyl moiety. After reacting with phosgene, APQ is converted to a new restricted intramolecular motion product APQU1 . Owing to the specific cyclization reactions, APQ exhibits an obvious fluorescence response toward phosgene with a large Stokes shift (104 nm), instant response (less than 20 s), and low detection limit (0.16 ppm). Moreover, the APQ -loaded test strip was prepared and demonstrated to have practical utility in detecting phosgene vapor.